IMPLEMENTASI METODE BACKWARD CHAINING PADA DATA WAREHOUSE DAOP 1 JAKARTA PT. KAI (PERSERO): Rakhmat Arianto, Chandra Bagus Sugiarto - Jurnal, Redaksi Tim; Haris, Abdul (PETIR, 2019)
Inventory data collection application is very helpful for the goods, procurement and reporting of goods by using the application checking the goods can be done easily with a model different from the inventory of old or traditional. Backward chaining expert system method is a method that is able to gave the final results or give a decision in accordance with the existing conditions in accordance with the wishes of the user. JAKARTA PT.KAI DAOP 1 covers the area from station to station Merak in Banten in West Java Cikampek crossing stations in Jakarta, Banten, Bogor, Depok, Sukabumi and Karawang in West Java. Demand for goods and property damage reports very closely linked with inventory application in DAOP 1 JAKARTA PT.KAI. It is the reason for the application is made is to maintain the availability of items, list of IT goods in the region DAOP 1 JAKARTA PT.KAI and this application contains the inventory data, the demand for goods. The report damage to the goods and the method of backward chaining system which provides the final result of decisions availability.